Downhill running regulates cardiac immune response through GCN2 - Xinyue Bai; Wanting Zhang; Yingyue Zhang; Xin Xu (PLoS ONE, 2025)
Downhill running (DR) has recently emerged as a promising exercise modality for cardiac rehabilitation, but the effect and mechanism of DR on myocardium remains unclear. General control nonderepressible 2 (GCN2), an eukaryotic initiation factor 2α (eIF2α) kinase, is beneficial to the heart when it is deficiency. The current study aimed to explore whether the GCN2 is associated with cardioprotective effects in downhill running. Eight-week-old male wild type (WT) mice and GCN2 knock out (KO) mice were randomly divided into WT control (n = 6), WT exercise(n = 5), GCN2 KO control(n = 5), and GCN2 KO exercise(n = 5) groups. Mice in the exercise groups were subjected to a single session of downhill running treadmill exercise training. In WT mice, DR increased the proportion of basophils, decreased the percentage of lymphocytes in the blood, and decreased the expression of GCN2, Ifn-γ, Tgf-βr1 and immune cell markers in the myocardium. Compared with WT mice, GCN2 KO mice decreased the proportion of monocytes and neutrophils in the blood, decreased expression of Ifn-γ, Tgf-βr1 and immune cell markers, and increased expression of Il-12α in the myocardium. In GCN2 KO mice, DR increased the expression of immune cell markers in the myocardium. DR and GCN2 KO both reduced TGF-β1 expression, and elevated p-eif2a expression in the myocardium. This finding demonstrated that downhill running alters inflammation and immune response in the myocardium, which is associated with GCN2.